I canti in memoria di Teraupoo e Matahi. Il ritorno degli eroi della guerra per l’annessione delle Isole Sottovento (Polinesia Francese) - Lattanzi, Francesco (L'Uomo Società tradizione sviluppo, 2021)
The songs in memory of Teraupoo and Matahi. The return of the war heroes against the annexation of the Leeward Islands (French Polynesia) Recently, in French Polynesia there has been an unprecedented enhancement of the figures who played a central role in the resistance of the French colonization, started in the second half of the Nineteenth century. This process also takes place through the Mā’ohi groups performances staged in the Heiva of Tahiti and other festivals in the various archipelagos. Reading the texts of traditional songs, called hīmene, performed at the festivals, and adopting them as useful sources for ethnographic analysis, it emerges how often the years of colonialism have been represented recently, whereas before, during the period of “cultural renaissance” of the Seventies and the Eighties, the topic had remained silenced due to its political position. Through the songs staged in 2002 at the Heiva of Tumara’a, the district of Ra’iātea where the last phase of the conflict for the French annexation of the Leeward Islands took place in 1897, I examine these dynamics, dwelling in particular on the return to the memory of the Mā’ohi of Teraupoo, guide of the anti-colonial struggle. The analysis of the lyrics represents one of the keys within which can the ethnographer deepen similar processes and reveal their contemporary effervescence, political implications, and different interpretations. Together with Teraupoo, another largely unknown protagonist, Matahi, is evoked in the staging of the conflict. In addition to the anti-colonial claims, Matahi’s “discovery” highlights the multiple interpretations that have crossed colonial history within the Mā’ohi society and that characterize his articulated memories today.